The Importance of Reading Literacy in Improving Students' Academic Achievement - Agiestianie, Eka; Jahongir, Teshayev; Firdaus, Fauzan Akmal (CV. Goresan Pena, 2025)
This study aims to examine the importance of reading literacy in improving students' learning achievement and the factors that influence it both from internal and external aspects. The method used is a descriptive qualitative approach with literature study, which involves collecting and analyzing various written sources such as books, journals, articles, and official documents related to reading literacy and learning achievement. The results of the study indicate that reading literacy not only plays a role in the ability to understand texts, but also contributes significantly to students' motivation and academic achievement. Internal factors such as motivation, reading habits, and language skills as well as external factors such as family support, school environment, and community greatly determine students' reading interest. This study also highlights the importance of collaboration between teachers, parents, and the community in creating an environment that supports a culture of literacy so that students are able to achieve optimal learning achievement. In conclusion, improving reading literacy must be the main focus in educational strategies to face the challenges of today's digital era.